Novel Approach to Assess Cardiac Function Using Systolic Performance and Myocardial Performance Indices From Simultaneous Electrocardiography and Phonocardiography Recordings in Dogs With Various Stages of Myxomatous Mitral Valve Disease - Gicana, Karlo Romano B.; Lertwanakarn, Tuchakorn; Tachampa, Kittipong (Frontiers in Veterinary Science, 2021)
Background and Objective: Myxomatous mitral valve disease (MMVD) progression entails changes in the structural and functional properties of the heart affecting cardiac timings and intervals within the cardiac cycle. Conventionally, echocardiography is used to determine the cardiac time intervals (CTIs) including systolic and myocardial performance indices (SPI and MPI) in evaluating cardiac function. Alternatively, these CTIs can also be measured using simultaneous recordings of electrocardiography (ECG) and phonocardiography (PCG), but their values in different MMVD stages remain to be established. This study aimed to establish and prove the use of derived SPI and MPI from a dedicated device as a novel approach to assess cardiac function in different stages of MMVD dogs. Materials and Methods: A prospective study in 52 dogs with different MMVD stages measured the CTIs using a novel device. These were compared and correlated with standard echocardiographic parameters. The predictive value of SPI and three new proposed formulas to estimate MPI (i.e., F1, F2, and F3) in association with asymptomatic from symptomatic MMVD dogs were investigated. Results: Our findings revealed that CTI parameters measured from a novel device including QS1, QS2, S1S2, MPI-F1, and MPI-F2 were altered at different stages of MMVD. The SPI and all proposed MPI formulas were comparable with the systolic time interval and Tei index from echocardiography. In addition, the SPI, MPI-F1, and MPI-F2 were significantly correlated with the Tei index. However, the SPI was not able to differentiate the various stages of MMVD. Conversely, only the MPI-F1 (i.e., (QS1 + S2)/S1S2) demonstrated good predictive accuracy when compared between asymptomatic and symptomatic MMVD dogs similar to the Tei index. Moreover, this formula was able to differentiate stages B1 and C with remarkable predictive accuracy, higher sensitivity, and high specificity when compared with the Tei index. Conclusion: We have successfully described the CTI parameters in different MMVD stages using simultaneous ECG and PCG recordings in dogs. Furthermore, we have proven that the concept of using the newly proposed parameters from a novel device is equivalent to the Tei index. Thus, we established a novel approach to evaluate cardiac function and its supportive use in the diagnosis of MMVD patients.